Slow food tourism: The mediating role of destination image in tourism motivation, satisfaction and competitiveness - Reyes Pradas, Laura (2022)
Slow food tourism has emerged as a recent topic in both the academic and the practical field. Studies reveal the role of food as a lifestyle market and a medium of cultural identification. Prior research identifies the involvement at the destination as the main goal of this new niche of tourism. However, there is limited knowledge of the current status of slow food tourism in different cities. This study, based on a sample of 206 tourists visiting the city of Valencia, develops and tests, using structural equation modeling (SEM), a conceptual model to assess the actual state of the slow food tourism within the city perceived by its tourists. Results indicate the importance of the destination image in mediating tourists satisfaction and Valencia!s competitiveness as a tourist destination, by highlighting the role of tourism motivation, involvement and touristic infrastructure on the tourist satisfaction and the destination competitiveness, mediated by the destination image that tourists hold in their minds about the place visited. Moreover, the authors also find contradictions on the variables. More specifically, study results confirm the negative relationship between tourism infrastructure, involvement and motivation regarding tourists satisfaction, which contradicts previous research. Findings of this study enrich existing literature by addressing the slow food tourism from a quantitative approach and in a new city and explore practical implications to the tourist entrepreneurs of Valencia, as well as future paths for research.